Magnetic field generation during intense laser channelling in underdense plasma - Smyth,AG; Sarri,G; Vranic,M; Amano,Y; Doria,D; Guillaume,E; Habara,H; Heathcote,R; Hicks,G; Najmudin,Z; Nakamura,H; Norreys,PA; et al. (Physics of Plasmas, 2016)
Channel formation during the propagation of a high-energy (120 J) and long duration (30 ps) laser pulse through an underdense deuterium plasma has been spatially and temporally resolved via means of a proton imaging technique, with intrinsic resolutions of a few μm and a few ps, respectively. Conclusive proof is provided that strong azimuthally symmetric magnetic fields with a strength of around 0.5 MG are created inside the channel, consistent with the generation of a collimated beam of relativistic electrons. The inferred electron beam characteristics may have implications for the cone-free fast-ignition scheme of inertial confinement fusion.